Development of a Website-Based Industrial Practice Management System - Alifya NFH; Ayu Tri Wardani (Journal of Electrical Engineering and Informatics, 2026)
This research aims to develop an integrated website-based Industrial Practice Management System (PI) to digitize the entire PI process, improve administrative efficiency, and support monitoring and evaluation of student activities. This research uses the Research and Development method with the Waterfall software development model. The development stages include needs analysis, system design, implementation, system integration and testing with the black box method. The system developed has features of assessment, provision, PI registration, daily logbook management, seminar submission, approval process, and the appointment of supervisors in one platform. Functional testing was conducted against 90 test scenarios covering 19 functional needs. The test results show that all scenarios obtain a status of "Suitable", which indicates a 100% success rate and proves that all system functions are running according to the user's needs. The novelty of this research lies in the development of an Industrial Practice Management System that integrates the entire PI cycle, in contrast to previous research which generally only focused on part of the PI process. This system supports comprehensive management, real-time monitoring, and multi-role collaboration involving students, PI admins, supervisors, and study program heads so as to improve the effectiveness and quality of Industrial Practice management in universities.